The susceptibility of single nucleotide polymorphisms located within co-stimulatory pathways to systemic lupus erythematosus - Chen, Ding-Ping; Lin, Wei-Tzu; Hsu, Fang-Ping; Yu, Kuang-Hui (Frontiers in Immunology, 2024)
Autoimmune diseases result from the loss of immune tolerance, and they exhibit complex pathogenic mechanisms that remain challenging to effectively treat. It has been reported that the altered expression levels of co-stimulatory/inhibitory molecules will affect the level of T/B cell activation and lead to the loss of immune tolerance. In this study, we evaluated the gene polymorphisms of the ligand genes corresponding co-stimulatory system that were expressed on antigen-presenting cells (CD80, CD86, ICOSLG, and PDL1) from 60 systemic lupus erythematosus (SLE) patients and 60 healthy controls. The results showed that rs16829984 and rs57271503 of the CD80 gene and rs4143815 of the PDL1 gene were associated with SLE, in which the G-allele of rs16829984 (p=0.022), the A-allele of rs57271503 (p=0.029), and the GG and GC genotype of rs4143815 (p=0.039) may be risk polymorphisms for SLE. These SNPs are in the promoter and 3'UTR of the genes, so they may affect the transcription and translation activity of the genes, thereby regulating immune function and contributing to the development of SLE.